Development of Ethnomathematics-Based Student Worksheets to Improve Conceptual Understanding - Nurul Ain Asnawati; Rusi Ulfa Hasanah (MASI Mandiri Edukasi, 2025)
Conceptual understanding is essential in geometry, yet many students struggle with rotation concepts due to a lack of contextual learning materials. This study aims to develop ethnomathematics-based student worksheets (LKPD) by integrating the Serampang Dua Belas dance movements as a rotation representation. The worksheets were tested on 37 ninth-grade students at an Islamic junior high school in Serdang Bedagai Regency using the ADDIE development model. Validation results from subject matter and media experts scored 89% (highly valid), while teacher and student responses indicated 89% (efficient). Effectiveness was demonstrated with an N-Gain of 0.77 (high category), and 82% of students scored ≥75. These findings confirm that the developed LKPD is valid, practical, and effective, offering an innovative learning tool that bridges mathematics with local culture and has the potential to be adapted to other cultural and mathematical contexts.